The Human Pancreas as a Source of Protolerogenic Extracellular Matrix Scaffold for a New-generation Bioartificial Endocrine Pancreas. Issue 1 (July 2016) - Peloso, Andrea; Urbani, Luca; Cravedi, Paolo; Katari, Ravi; Maghsoudlou, Panagiotis; Fallas, Mario Enrique Alvarez; Sordi, Valeria; Citro, Antonio; Purroy, Carolina; Niu, Guoguang; McQuilling, John P.; Sittadjody, Sivanandane; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: Our study aims at producing acellular extracellular matrix scaffolds from the human pancreas (hpaECMs) as a first critical step toward the production of a new-generation, fully human-derived bioartificial endocrine pancreas. In this bioartificial endocrine pancreas, the hardware will be represented by hpaECMs, whereas the software will consist in the cellular compartment generated from patient's own cells. Background: Extracellular matrix (ECM)-based scaffolds obtained through the decellularization of native organs have become the favored platform in the field of complex organ bioengineering. However, the paradigm is now switching from the porcine to the human model. Methods: To achieve our goal, human pancreata were decellularized with Triton-based solution and thoroughly characterized. Primary endpoints were complete cell and DNA clearance, preservation of ECM components, growth factors and stiffness, ability to induce angiogenesis, conservation of the framework of the innate vasculature, and immunogenicity. Secondary endpoint was hpaECMs' ability to sustain growth and function of human islet and human primary pancreatic endothelial cells. Results: Results show that hpaECMs can be successfully and consistently produced from human pancreata and maintain their innate molecular and spatial framework and stiffness, and vital growth factors. Importantly, hpaECMs inhibit human naïve CD4 + T-cell expansion in response to polyclonal stimuli by inducing their apoptosis and promoting their conversion into regulatory T cells. hpaECMs are cytocompatible and supportive of representative pancreatic cell types. Discussion: We, therefore, conclude that hpaECMs has the potential to become an ideal platform for investigations aiming at the manufacturing of a regenerative medicine-inspired bioartificial endocrine pancreas.